Hubungan Antara Beban Kerja Perawat dengan Motivasi Pelaksanaan Dokumentasi Asuhan Keperawatan di Irna I RSU Dr Saiful Anwar Malang - Titik Sri Rahayu; Wiwik Agustina; Sih Ageng Lumadi (Universitas Batanghari Jambi, 2022)
The high number of COVID-19 cases in December 2020 caused 3,233 people to be infected. 303 of those people underwent treatment at the dr. Saiful Anwar Malang Public Hospital as a COVID-19 referral hospital. As a result, this phenomenon caused a surge in bed occupancy capacity of 85%-100%, so that it increased the nurse workload. This research aimed to understand the relationship between the nurse workload and the motivation to implement nursing training documentation at IRNA I dr. Saiful Anwar Malang Public Hospital. The research method applied was correlational research with a cross-sectional approach. This method aimed to determine the relationship between the nurse workload and the motivation to implement nursing training documentation. The sample consisted of 55 people who were chosen by total sampling. The variable studied in this research was the nurse workload with the motivation to implement nursing training documentation. The results showed that most of the respondents had a high workload, which was as many as 27 people (67.5%), and the motivation to implement nursing training documentation was primarily high, which was as many as 33 people (82.5%). However, when the workload was very high, and 6 respondents experienced it, the motivation decreased by 12, 5%. The results of Spearman's analysis and statistical test, p = -0.378 at = 0.05, indicated that there was a significant correlation between the variables. The direction of the negative correlation indicated that the higher the workload of nurses, the lower the motivation in conducting nursing training documentation. Therefore, it is necessary to balance the availability of nurses and the workload so that the quality of the nursing services can be reached.